Effect of shenmai injection on anthracycline-induced cardiotoxicity: A systematic review and meta-analysis - Lili Yang; Xiaorui Liu; Wen Yang; Siqi Wang; Zimu Li; Yiming Lei; Dongling Liu (Elsevier, 2024)
Objective: Shenmai injection is a classic herbal prescription, and is often recommended for the treatment of anthracycline-induced cardiotoxicity. However, the efficacy and safety of Shenmai injection for the treatment of anthracycline-induced cardiotoxicity have not been reported. Materials and methods: We conducted a comprehensive search of eight literature databases and two clinical trial registries, retrieving all randomized controlled trials (RCTs) related to the treatment of anthracycline-induced cardiotoxicity with Shenmai injection from the establishment of the databases to July 1, 2023. Data analysis was performed using the Meta package in RStudio and RevMan 5.4. The GRADE pro3.6.1 software was utilized for assessing the quality of evidence. Results: A total of 16 RCTs including 2140 patients were included in this study. Meta-analysis showed that Shenmai injection had an advantage in improving ST-T segment changes (RR = 0.28; 95 % CI, 0.20 to 0.39; P < 0.0001) (P < 0.01), creatine kinase isoenzyme (SMD = −3.49; 95 % CI, −5.24 to −1.74; P < 0.0001), Prolonged QT interval (RR = 0.46; 95 % CI, 0.28 to 0.75; P = 0.0018), Low QRS Voltage (RR = 0.44; 95 % CI, 0.27 to 0.71; P = 0.0007), sinus tachycardia (RR = 0.41; 95 % CI, 0.28 to 0.60; P < 0.0001), atrial premature beats (RR = 0.55; 95 % CI, 0.35 to 0.87; P = 0.01), Premature Ventricular Contractions (RR = 0.39; 95 % CI, 0.26 to 0.59; P < 0.0001) and creatine kinase (SMD = −1.43; 95 % CI, −2.57 to −0.29; P < 0.0001) in patients with anthracycline-induced cardiotoxicity. advantage, which was supported by sensitivity analyses, but not in improving left ventricular ejection fraction (MD = 16.01; 95 % CI, −3.10 to 35.12; P = 0.10) and atrioventricular block (RR = 0.49; 95 % CI, 0.24 to 1.03; P = 0.06). The literature included in the study did not refer to data regarding the safety aspects of Shenmai injection, so we do not yet know the safety of Shenmai injection. The results of subgroup analyses suggested that heterogeneity was not related to the administered dose and chemotherapy regimen. The publication bias test showed no publication bias. The quality of evidence for the results ranged from "very low" to "moderate." Conclusion: This study suggests that Shenmai injection is effective in treating anthracycline-induced cardiotoxicity and is a potential treatment for anthracycline-induced cardiotoxicity. However, due to the poor methodological quality of the included RCTs, we recommend rigorous, high-quality, large-sample trials to confirm our findings.